"Little more than a gut feeling?"—considerations when prescribing psychotropic medications to patients undergoing bariatric surgery. (June 2021) - Braun, Anastasia; Bruxner, George
Objective: Bariatric surgical procedures are being commonly performed increasingly, and many surgical candidates are concomitantly taking psychotropic medication. This paper aims to elucidate issues when prescribing psychiatric medication in this setting of substantial anatomical and physiological change. Method: A hand search of the literature to assess the current understanding of effects of various bariatric procedures on the bioavailability of psychotropic medication. Results: Predominantly malabsorptive bariatric procedures may reduce bioavailability of some but not all commonly used psychiatric medications. There is minimal information about the effects of the most commonly performed surgery, vertical sleeve gastrectomy. Lithium prescription and monitoring requires caution. Conclusions: There is limited guidance for prescription for psychotropic medication in the bariatric surgery patient group, and vigilance for unexpected adverse effects or altered efficacy is warranted.